Application of Cloud Computing Technology to Improve Academic Information System Performance in Computer Science Program - Jayaun; Suharmanto; Sitti Aliyah Azzahra (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
The increasing demand for efficient, scalable, and reliable academic services has encouraged higher education institutions to adopt innovative information technology solutions. This research provides originality by examining the implementation of Cloud Computing technology as a strategic approach to improving academic information system performance, particularly in the Master’s Program of Computer Science. The objective of this study is to analyze the role of Cloud Computing in enhancing system efficiency, accessibility, scalability, and data management quality. This research employs a quantitative approach by evaluating academic information system performance indicators before and after the adoption of cloud-based technology. Data were collected through system performance analysis and user evaluation to identify the impact of Cloud Computing implementation. The empirical results indicate that Cloud Computing improves academic information system performance through faster data processing, better resource optimization, increased accessibility, and enhanced operational efficiency. However, several challenges, including data security management and user adaptation, should be considered during implementation. The findings imply that Cloud Computing can serve as an effective technological framework for supporting digital transformation and improving the quality of academic services in higher education institutions.